RELIGIOUS ANCIENT MANUSCRIPT IN THE CITY OF TIDORE ISLAND, NORTH MALUKU PROVINCE - Idham Khalid Bodi (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
The research of mapping, inventory, and digitalization of the religious ancient manuscript conducted in City of Tidore Island, requiring the search of hand written manuscript that is still kept in the society as an affort to preserve the ancient manuscript in the form of transfering to textual media into digital form, and can provide an general overview about the manuscripts that is still exist around the society area, through the manuscript codicology approach. This research found 106 religious manuscript consist of seven owner of manuscripts spreading in Tidore Island and Maitara Island. The manuscripts generally contain teachings of tasawwuf that are inherited from teacher to follower, zikir and prayers, as well as some qoutes of Qur'anic verses. The sacralization of the manuscript is still quite visible in the Tidore society, not all the manuscripts owner willing to show the manuscript to be read because of the fear, and any other reasons. This research also sees the existence and sustainability of religious manuscript in Tidore and Maitara is still maintained, it can be seen through the system of transformation of tasawuf knowledge between teachers and students that requiring recopying should be handwritten on the main subjects of tasawuf for the blessing of transferred science.